Knowledge about the prevalence of blood-transmitted diseases among lower secondary school students - Waszkiewicz, Ludmiła; Połtyn-Zaradna, Katarzyna; Zatońska, Katarzyna; Holka, Bożena; Einhorn, Jakub (Polish Journal of Public Health, 2010)
Introduction. In Poland estimate that number of HBS vectors is about 1.5 million persons, and a sign of infection – anti HBC antibody – is detected in approximately 10% of the population, and a number of active replicating and infected vectors is over 500 thousand peoples. We estimate that in Poland almost 800 thousand peoples are infected with hepatitis C virus (HCV). In Poland, from 1985 to 31 March 2008, infection with HIV was detected in 1,1431 Polish citizens, 2,052 of which developed the acquired immunodeficiency syndrome (AIDS).Aim. The aim of the study was to examine the of knowledge among young people from the lower secondary school about prevention of diseases connected with blond, such as infection with hepatitis B virus (HBV), hepatitis C virus (HCV) and human immunodeficiency virus (HIV).Material and method. An anonymous questionnaire study was carried out in 2006/2007 school year among 100 3rd-grade lower secondary school students. The result of the research was analyzed with respect to sex.Results. Almost all of the students (94%) know that HBV, HCV and HIV are diseases connected with blood. Girls presented a better understanding of the ways that infections can spread. Only 16 students indicated the optimum answer concerning HBV prevention, 10 students optimally answered the questions concerning HCV prevention, and 30 – those related to HIV/AIDS. A higher level of knowledge of prevention against HBV, HCV, and HIV was presented by girls. Less than a third of the students surveyed estimated their knowledge level of prevention as insufficient, while more than half of the students (59%) believed that the sufficient knowledge on prevention against HBV, HCV and HIV will protect them from infecting.Conclusion. It would be advisable to intensify activities in the field of health education, with particular emphasis on blood-transmitted infections, and to aim the education on blood transmitted infections at the students’ parents.